Comparison of three essential sub-micrometer aerosol measurements: Mass, size and shape. Issue 10 (2nd October 2020) - Yao, Qi; Asa-Awuku, Akua; Zangmeister, Christopher D.; Radney, James G.
Abstract: An instrumental trifecta now exists for aerosol separation and classification by aerodynamic diameter ( D ae ), mobility diameter ( D m ) and mass ( m ) utilizing an aerodynamic aerosol classifier (AAC), differential mobility analyzer (DMA) and aerosol particle mass analyzer (APM), respectively. In principle, any combination of two measurements yields the third. These quantities also allow for the derivation of the particle effective density ( ρ eff ) and dynamic shape factor ( χ ). Measured and/or derived deviations between tandem measurements are dependent upon the configuration but are generally <10%. Notably, nonphysical values of χ (<1) and ρ eff (>bulk) were determined by the AAC-APM. Harmonization of the results requires the use of χ in the determination of m and D m from the AAC-DMA and AAC-APM requiring either a priori assumptions or determination from another method. Further errors can arise from assuming instead of measuring physical conditions – e.g., temperature and pressure affect the gas viscosity, mean free path and the Cunningham slip correction factor therefore impacting D m and D ae – but are expected to have a smaller impact than χ . Utilizing this triplet of instrumentation in combination allows for quantitative determination of χ and the particle density ( ρ p ). If the bulk density is known or assumed, then the packing density can be determined. The χ and ρ p were determined to be 1.10 ± 0.03 and (1.00 ± 0.02) g cm −3, respectively, for a water stabilized black carbon mimic that resembles aged (collapsed) soot in the atmosphere. Assuming ρ bulk = 1.8 g cm −3, a packing density of 0.55 ± 0.02 is obtained. Copyright © 2020 American Association for Aerosol Research